Electrochemically assisted photocatalytic degradation of 4-chlorophenol by ZnFe2O4-modified TiO2 nanotube array electrode under visible light irradiation - Hou, Y.; Li, Xin Yong; Zhao, Q.; Quan, X.; Chen, G. (American Chemical Society, 2010)
A well-aligned ZnFe2O4/TiO2 composite nanotube array (ZnFe2O4/TiO2-NTs) electrode with visible-light activity was successfully prepared using a two-step electrochemical process of anodization and a novel cathodic electrodeposition method followed by annealing. The ZnFe2O4 nanoparticles were highly dispersed inside the TiO2-NTs but minimized at the tube entrances. The structure and optical properties of the TiO2 nanotubes and the derived composites have been well characterized. The composites displayed a strong photo response in the visible region and low recombination rate of the electron-hole pairs. In addition, the synthesized ZnFe 2O4/TiO2-NTs electrode showed much higher photocurrent density in the visible region than pure TiO2-NTs electrode. The dramatically enhanced electrochemically assisted photocatalytic activity of the composite electrode was evaluated in the decomposition of 4-chlorophenol and dichloroacetate under visible light irradiation (420 nm < ? < 600 nm). The improved photoelectrocatalytic (PEC) activity is derived from the synergetic effect between ZnFe2O4 and TiO2, which promoted the migration efficiency of photogenerated carriers at the interface of the composite and enhanced the efficiency of photon harvesting in the visible region. The degradation of 4-chlorophenol was monitored by measuring Cl- concentrations and analyzing reaction intermediates by high-performance liquid chromatography-mass spectroscopy (HPLC-MS). © 2010 American Chemical Society.